NAVIGATING THE CHALLENGES OF DOCTORAL JOURNEY: VOICES OF THE STUDENTS PURSUING THEIR STUDIES ABROAD - Waheed, Syed Abdul (Journal of Arts & Social Sciences, 2022)
Doctoral students face certain difficulties and challenges while participating in academic and research activities during the course of their PhD studies in a foreign university. They make attempts to seek cooperation from the academic communities to find a way out and to cope with the emerging situation. The present study aims to examine doctoral students’ experiences of such difficulties and challenges, their experiences with the language while engaged in their doctoral studies, orientation to their study program, and the academic environment of the university. A phenomenological approach was used to explore doctoral students’ experiences. Fifteen participants were purposively selected from public sector universities located in different cities in Austria. They were interviewed and field notes were taken. The interview transcripts were analyzed by reading the text several times and identifying the emerging themes. The finding of the study revealed that most of the difficulties and challenges were a function of the lack of preparation before coming to Austria, the relatively different academic and research culture of the host universities, and a lack of orientation to the university system after arrival. Learning the German language was found to be significant in social life but it was not a challenge in the academic life of the students within the university. The study has implications for international students who should plan their studies, get an orientation to the studies immediately after arrival, and should be flexible in learning the language for social and academic integration.